2009
DOI: 10.1038/nature08461
|View full text |Cite
|
Sign up to set email alerts
|

An anatomical signature for literacy

Abstract: Language is a uniquely human ability that evolved at some point in the roughly 6,000,000 years since human and chimpanzee lines diverged. Even in the most linguistically impoverished environments, children naturally develop sophisticated language systems. In contrast, reading is a learnt skill that does not develop without intensive tuition and practice. Learning to read is likely to involve ontogenic structural brain changes, but these are nearly impossible to isolate in children owing to concurrent biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
278
3
10

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 387 publications
(310 citation statements)
references
References 44 publications
19
278
3
10
Order By: Relevance
“…(2010) and Carreiras et al . (2009)). Analogous to this, adult illiterates are shown to have improved their phonological skills after having learned to read and write (Morais, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…(2010) and Carreiras et al . (2009)). Analogous to this, adult illiterates are shown to have improved their phonological skills after having learned to read and write (Morais, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Literacy is perhaps the most remarkable perceptual-learning experience in modern societies 63 . It is a radical transformation, after which a set of visual symbols becomes automatically mapped to auditory phonemes.…”
Section: R E V I E Wmentioning
confidence: 99%
“…Dougherty et al (2007), Robichon and Habib (1998), and Rumsey et al (1996) all reported reduced white matter in the corpus callosum. Carreiras et al (2009) concluded in their paper that white matter differences in the corpus callosum are likely to be a consequence of differences in reading experience rather than the cause of reading difficulties. We agree.…”
Section: Structural Imagingmentioning
confidence: 99%
“…This suggests that acquiring reading and writing skills at the appropriate age shapes not only the morphology of the corpus callosum and the corresponding interhemispheric connectivity but also the pattern of interaction between the interconnected inferior parietal regions. Carreiras et al (2009) compared illiterates with individuals who acquired reading late in life and also observed a greater amount of white matter in the splenium of the corpus callosum. These results strongly suggest that reading experience strengthens white matter pathways in the corpus callosum.…”
Section: Structural Imagingmentioning
confidence: 99%